Aplikasi Kurikulum Merdeka Belajar-Kampus Merdeka (MBKM) pada Perguruan Tinggi Terhadap Karier Mahasiswa - Rachma Syifa Aryanti; Whisnu Yudiana; Rezki Ashriyana Sulistiobudi (Jurnal Paedagogy, 2023)
This study aims to analyze the role of career exploration on students' career maturity with different MBKM and non-MBKM curricula. This study used a quantitative approach with correlational research methods. The Career Exploration Scale (CES) and the Career Development Inventory (CDI) were used as measurement instruments in this study (CDI). The population of this research was active students with the non-MBKM curriculum (n=144) and active students with the MBKM curriculum (n=147). Both populations were from a university in Bandung's Faculty of Psychology. Data was collected from students with a non-MBKM curriculum (n=108) and students with the MBKM curriculum (n=111) of the Faculty of Psychology from a university in Bandung, with a probability sampling technique, namely simple random sampling. The data analysis techniques used in this research were regression and covariance analysis. The results showed a role for career exploration in career maturity in the non-MBKM and the MBKM curricula. The role of career exploration on career maturity differs between the two populations. It indicated that the curriculum significantly influences student careers, whereas the MBKM curriculum was more effective in preparing student careers.